The Effect of Hydrogel and Compost on Hydric Characteristics of Sandy Soil and Its Effect on Tomato Emergence - Barakat, Mona; Suleiman, Sawsan; Wanoos, Simon (Latakia University Journal -Biological Sciences Series, 2013)
The research investigated the effect of treating sandy soil with (0.1-0.2-0.3%) hydrogel and (1-2-3%)tobacco waste composton sandy soil hydric characteristics, and the factors affecting polymer capacity to absorb water. The results showed the efficiency of both hydrogel and compost in saving water in sandy soil. The infiltration rate decreased to(48-50-57%)when the soil was treated with different concentrations of hydrogel,and to(29-32-36%)when the soil was treated with different concentrations of compost respectively. Whereas Field capacity increased with hydrogel treatment up to (39-52-59%)and the permanent wilting point was delayed for (2,4,and 5 days)compared to the control, the increase in the field capacity with compost treatment was(32-46-56%)respectively and the delay in plant wilting point was(1, 3and 4 days) compared to the control.The results revealed that the quantity of water absorbed by the polymer decreases when water salt concentration increases, and that the quantity of water absorbed by the polymer mixed with the soil is less than the quantity of water absorbed by the polymer alone.